2018
DOI: 10.31083/jin-170050
|View full text |Cite
|
Sign up to set email alerts
|

Gsk3β aggravates the depression symptoms in chronic stress mouse model

Abstract: Depression caused by genetic and environmental factors is acomplicated disease. Here, it is demonstrated that glycogen synthase kinase-3β is highly expressed and phosphorylated in the brain of a chronic stress mouse. Inhibition of glycogen synthase kinase-3β leads to decreased depression-like symptoms which manifest in open-field test, tail-suspension test, forcedswim test, and a novelty suppressed feeding test. It was also found that β -catenin is attenuated, and its target genes Cyclin D1 and c-Myc are down-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…The target-pathway network illustrated that AKT1, MAPK1, GSK3B, TNF, MTOR, and PTEN were core targets enriched in key signaling pathways that played crucial roles in the treatment of depression by CCHP. GSK3B may be involved in the development of depression by inhibiting Erk-CREB-BDNF signaling [ 99 ], and PI3K/Akt/mTOR/GSK3B signaling may be the mechanism underlying the rapid antidepressant effects [ 100 ]. TNF polymorphisms are associated with depression [ 65 ], and the suppression of TNF- α /TNFR1/NF- κ B signaling alleviated neuroinflammation and depression [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…The target-pathway network illustrated that AKT1, MAPK1, GSK3B, TNF, MTOR, and PTEN were core targets enriched in key signaling pathways that played crucial roles in the treatment of depression by CCHP. GSK3B may be involved in the development of depression by inhibiting Erk-CREB-BDNF signaling [ 99 ], and PI3K/Akt/mTOR/GSK3B signaling may be the mechanism underlying the rapid antidepressant effects [ 100 ]. TNF polymorphisms are associated with depression [ 65 ], and the suppression of TNF- α /TNFR1/NF- κ B signaling alleviated neuroinflammation and depression [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PPARα, there are a lot of other proteins that not only control BDNF biosynthesis and neuroplasticity but also are implicated in depression, such as salt-inducible kinase 2, glycogen synthase kinase 3β and mammalian target of rapamycin ( Zhou et al, 2014 ; Peng et al, 2018 ; Jiang et al, 2019 ). These proteins may also play a role in the antidepressant actions of vortioxetine, and more extensive research will be exhibited in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is a multifunctional serine/threonine protein kinase that contributes to diverse cell functions, including gene expression, neurogenesis, neuroplasticity, cell survival, differentiation, migration, stress responses, and apoptosis, in the immune system, neurotransmitter systems, metabolism, and other functions (Hur and Zhou, 2010;Valvezan and Klein, 2012). GSK-3B has been found to mediate depressive symptoms in a chronic stress mouse model (Peng et al, 2018), and its inhibition has been shown to produce antidepressant-like effects in other animal models of depression (Gould et al, 2004;Kaidanovich-Beilin et al, 2004). Variation in grey matter volume in the hippocampus and superior temporal gyrus of depressed subjects has been associated with GSK3B polymorphisms (Inkster et al, 2009), and, in a post-mortem study of 20 depressed and 20 non-depressed subjects, Karege and collaborators found significant differences in protein levels of GSK-3B and β-catenin (Karege et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The canonical Wnt signaling pathway has garnered data that make it a promising system to explore in mood disorder research as well (Duman and Voleti, 2012). In psychiatry, evidence has accumulated on the participation on the Wnt signaling pathway in several diseases and related phenotypes (Mulligan and Cheyette, 2017) such as schizophrenia, (Miyaoka, Seno and Ishino, 1999;Levchenko et al, 2015;Hoseth et al, 2018), bipolar disorder (BD) (Matigian et al, 2007;Zandi et al, 2008;Sani et al, 2012;Winham et al, 2014;Pandey et al, 2015;Cuellar-Barboza et al, 2016;Hoseth et al, 2018), anxiety disorders (Zhao et al, 2018;Vidal et al, 2019), and depression (Saus et al, 2010;Enatescu et al, 2016;Peng et al, 2018;Vidal et al, 2019). Several members of the Wnt signaling pathway have been specifically linked to mood disorders.…”
Section: Introductionmentioning
confidence: 99%